2014
DOI: 10.1099/jmm.0.071449-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the growth dynamics and biofilm formation of Staphylococcus epidermidis strains isolated from contaminated platelet units

Abstract: Bacterial contamination of platelet concentrates (PCs) poses the highest transfusion-associated infectious risk, with Staphylococcus epidermidis being a predominant contaminant. Herein, the growth dynamics of 20 S. epidermidis strains in PCs and regular media were characterized. Strains were categorized as fast (short lag phase) or slow (long lag phase) growers in PCs. All strains were evaluated for the presence of the biofilm-associated icaAD genes by PCR, their capability to produce extracellular polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…In this study, we demonstrate that a combination of synthetic AMPs is effective in inhibiting biofilm formation by three biofilm‐forming strains of S. epidermidis in PCs. Previously, we have shown that the PC storage environment promotes biofilm formation by S. epidermidis isolates traditionally considered to be biofilm‐negative . Importantly, biofilms formed in PCs have increased pathogenicity as demonstrated using nematode‐killing assays .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In this study, we demonstrate that a combination of synthetic AMPs is effective in inhibiting biofilm formation by three biofilm‐forming strains of S. epidermidis in PCs. Previously, we have shown that the PC storage environment promotes biofilm formation by S. epidermidis isolates traditionally considered to be biofilm‐negative . Importantly, biofilms formed in PCs have increased pathogenicity as demonstrated using nematode‐killing assays .…”
Section: Discussionmentioning
confidence: 92%
“…It is also acknowledged that clinical studies in humans are needed before the use of AMPs have a practical application in transfusion settings. It is nevertheless important to highlight that bacterial detection during PC screening would be enhanced by using AMPs since we have demonstrated that biofilm formation during PC storage results in missed detection with culture systems . We have also shown that biofilms formed during PC storage have enhanced pathogenicity and could pose a higher safety risk to transfusion patients, which would be averted by inhibiting biofilm formation with AMPs.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations